ANALISIS NILAI PRODUKSI INDUSTRI ALAS KAKI DI INDONESIA PERIODE 2004-2013 - Maria Christina Panjaitan; Azwar Harahap; Sri Endang Kornita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
thefootwear industry in Indonesia period 2004-2013.Data used in this research is secondary data obtained from the Ministry of Industry of the Republic of Indonesia, Statistics Indonesia and the results processed authors themselves. The analysis method used in this study is deskriprtif and quantitativemethods, namely a method of partial and simultaneous analysis using SPSS 21.Based on the results of multiple regression analysis, the independent variables simultaneously affect simultaneously with a significance level of 0.05% of thevalue of production. Given also the coefficient of determination obtained for 0950 means that the influence of independent variables on the dependent variable of 95.0% and the remaining 5.0% is influenced by factors beyond the study.Partially known that the variable capital having the most significant effect on the value of production of the footwear industry in Indonesia. While the business units does not significantly influence the value of production of the footwear industry in Indonesia.Keywords:Business units, Labor, Capital, and Value Production